Near-infrared fluorescent probes based on naphthyridine derivatives for mitochondrial nucleic acid imaging - Ma, Huan; Ni, Wen-Pei; Lin, Qi; Sun, Ru; Ge, Jian-Feng (Analyst (London), 2025)
Most current nucleic acid-responsive fluorescent probes are enhanced ones with short emission wavelengths. Therefore, the development of novel near-infrared, turn-on response nucleic acid fluorescent probes is of great significance. Herein, three cationic fluorescent dyes 1a-1c were synthesized by reacting naphthalidine salt with suitable aldehydes. These probes exhibited excellent photostability, maintaining over 95% of their absorption rate after 5 h of irradiation. Notably, probes 1a-1c exhibited an OFF-ON fluorescence response to DNA and RNA. The maximum emission wavelength could reach the near-infrared region (661-762 nm), with large Stokes shifts (153-222 nm) upon binding to DNA/RNA. The fluorescence intensity was enhanced 143 fold and 127 fold for 1b upon interaction with DNA and RNA, respectively. Co-staining and nucleic acid digestion assays showed that probes 1a-1c could target the mitochondria of fixed cells with low cytotoxicity. These findings may be useful for the early screening of genetic mutations related to mitochondrial diseases. Fluorescent probes based on naphthyridinium salt derivatives exhibit OFF-ON fluorescence response to DNA/RNA.